Optimasi pH dan Ukuran Partikel Karbon Aktif dari Kulit Pisang Kepok (Musa balbisiana Colla) Terhadap Penyerapan Zat Warna Methylene Blue - Ridho Hermawan; Edi Nasra; Ananda Putra; Sri Benti Etika (Jurnal Periodic Jurusan Kimia UNP, 2022)
Methylene blue is one of the textile industry wastes which can cause pollution to aquatic ecosystems. The threshold value for the permissible concentration of methylene blue in ambient waters (5-10) mg / L. So we need a method to treat wastewater contaminated with dye so that it is safe to dispose of and does not pollute the environment. One of the effective methods for removing dye waste is the adsorption method. The purpose of this study was to determine the optimum absorption conditions and maximum absorption capacity of methylene blue using activated carbon from the peel of a banana (Musa balbisiana Colla). In this study, using the Bacht method to adsorb methylene blue dye by varying the pH and stirring speed. The results of this study showed that the absorption capacity at the optimum conditions of pH 6 and a particle size of 250 µm was 5.4096 mg / g and the absorption percentage was 86.54%.